GA3-MEDIATED DORMANCY ALLEVIATION IN THE REPUTED AFRICAN POTATO, HYPOXIS HEMEROCALLIDEA - Shaik, Shakira; Leanya, M.; Leanya, Moeketsi (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Hypoxis hemerocallidea, arguably the most well-known medicinal species in South Africa, has been the subject of intensive harvesting from the wild leading to recent conservation concerns. The seeds of this species do not propagate easily and can lie dormant for up to twelve months. Experiments using water, acid and chemical pre-sowing treatments were performed to determine the germination response of this species. Highest levels of germination (36.7-60.0% in the light and 36.7-46.7% in the dark) were achieved by treating mechanically scarified seeds with GA3 at various concentrations for 24 h. This was followed by scarified seeds soaked in water (26.7% in the light and 23.3% in the dark). Similar results (23.3 and 26.7%) were obtained in the 1% and 4% KNO3 treatments, respectively, under light conditions only. The fastest time to germinate was two days and was obtained in the 1200 ppm GA3 treatment in both light and dark conditions. H. hemerocallidea displays physical and non-deep physiological dormancy where pre-sowing treatments are required before the seeds will germinate.